2021
DOI: 10.1111/os.12980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F‐FDG PET/CT and 68Ga‐DOTATATE PET/CT in the Targeted Imaging of Culprit Tumors Causing Osteomalacia

Abstract: Objective To assess and compare the performance of fluorine‐18‐labeled fluorodeoxyglucose positron emission tomography (18F‐FDG‐PET/ CT) and gallium‐68‐labeled tetraazacyclododecanetetraacetic acid‐DPhe1‐Tyr3‐octreotate (68Ga‐ DOTATATE) PET/CT in the targeted imaging of culprit tumors causing osteomalacia. Methods This was a clinical retrospective analysis. We analyzed 13 patients (five men, eight women; mean age, 49 years; range, 19–55 years) with suspicion of tumor‐induced osteomalacia (TIO) between March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…( 8 ) and Yu et al. ( 22 ) reported similar high sensitivity, specificity, and accuracy in the detection of TIO. In contrast, several studies demonstrated a similar high diagnostic accuracy of 68 Ga-DOTA-NOC and 68 Ga-DOTA-TOC for the localization of TIO ( 4 , 5 , 11 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…( 8 ) and Yu et al. ( 22 ) reported similar high sensitivity, specificity, and accuracy in the detection of TIO. In contrast, several studies demonstrated a similar high diagnostic accuracy of 68 Ga-DOTA-NOC and 68 Ga-DOTA-TOC for the localization of TIO ( 4 , 5 , 11 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 77%
“…As displayed in Table 2, several studies have reported high TIO detection rates with 68 Ga-DOTA-TATE PET/CT, ranging from 83% to 100% (6,7,15,20,(23)(24)(25)(26)(27). Zhang et al (8) and Yu et al (22) reported similar high sensitivity, specificity, and accuracy in the detection of TIO. In contrast, several studies demonstrated a similar high diagnostic accuracy of 68 Ga-DOTA-NOC and 68 Ga-DOTA-TOC for the localization of TIO (4,5,11,28,29).…”
mentioning
confidence: 90%
See 1 more Smart Citation